Lysosomal glycosphingolipid catabolism by acid ceramidase: formation of glycosphingoid bases during deficiency of glycosidases - Ferraz, Maria J.; Marques, André R. A.; Appelman, Monique D.; Verhoek, Marri; Strijland, Anneke; Mirzaian, Mina; Scheij, Saskia; Ouairy, Cécile M.; Lahav, Daniel; Wisse, Patrick; Overkleeft, Herman S.; Boot, Rolf G.; et al. (FEBS letters, 2016)
Glycosphingoid bases are elevated in inherited lysosomal storage disorders with deficient activity of glycosphingolipid catabolizing glycosidases. We investigated the molecular basis of the formation of glucosylsphingosine and globotriaosylsphingosine during deficiency of glucocerebrosidase (Gaucher disease) and α‐galactosidase A (Fabry disease). Independent genetic and pharmacological evidence is presented pointing to an active role of acid ceramidase in both processes through deacylation of lysosomal glycosphingolipids. The potential pathophysiological relevance of elevated glycosphingoid bases generated through this alternative metabolism in patients suffering from lysosomal glycosidase defects is discussed.